Kajian Pemindahan Penumpukan Peti Kemas (Overbrengen) Ke Tempat Penampungan Sementara Di Pelabuhan Tanjung Priok - Khafendi, Khafendi (Warta Penelitian Perhubungan, 2010)
Port ofTanjung Priok, including the Jakarta International Container Terminal (JICT) and TerminalContainer (TPK) Koja is still ouersluuiowed lnj the potentinl density of container, container imports,especial.Ly in the yard because of among others, the ourners of the goods out slow and limited goodspage and ease of transportation where . bemuse of slow spending container and goods, especiallyimports of container. Page Contniner capacity is not proportional to the volume of imported goodsthat come in, so that the Yard Occupanci; Ratio (Jordan) could not be maintained in safe condition, sothat the importer is required to delete or mmJe a crate container page (cnJerbrengen)Causes of densiti; in the yard, especially on big dm;s like Eid, because, many basic needs before majorJwlidm;s or dm;s, as ItJell as a large carrier equipment (trucks) are forbidden to operate on the mainroad or track bnck and forth before the lwlidny or dny large/ Eid lwlidm;s and after (H-7 and H +),research was conducted with the compamtin~ 111et/10d to the field cumulation in when the big dm; andduring a nonnal dm;. To cnJercome the density of buildup, it slwuld be done several wm;s, amongothers, ln; the removal of container from page to another place (cnierbrengen) and increase the accumulationof container faci.lities at the port.Keywords : Container yard, Overurengen